Polygenic and autosomally inherited dimethoate resistance in Amrasca biguttula biguttula with no cross-resistance to bifenthrin, imidacloprid, and chlorfenapyr. (January 2023) - Khalid, Iqra; Mohsin, Muhammad; Abubakar, Muhammad; Ali Shad, Sarfraz; Binyameen, Muhammad
Abstract: The cotton jassid, Amrasca biguttula biguttula (Ishida) (Cicadellidae: Homoptera), is a polyphagous pest that infests many field crops, vegetables, and ornamental plants. It sucks sap from leaf tissues and also serves as a vector for hopper burn viral disease. A. biguttula has developed low to high levels of resistance to several insecticides. Because dimethoate is still widely used for management of this pest, this study was conducted to improve insecticide resistance-management (IRM) strategies by determining the genetics of dimethoate resistance in A. biguttula and its cross-resistance potential to bifenthrin, imidacloprid, and chlorfenapyr . A population was selected with dimethoate using the leaf dip method. After nine continuous cycles of selection with dimethoate, the selected population (Di-SEL) of A. biguttula developed a 90-fold level of resistance to this compound compared to the susceptible population. Dimethoate resistance in A. biguttula biguttula was transferred from parents to its offspring as an autosomal and incomplete dominant trait. The realized heritability value of dimethoate resistance was 0.17. The cross-resistance results showed that there was no cross-resistance to bifenthrin, imidacloprid, and chlorfenapyr. Our findings provide the basic knowledge to develop an improved IRM strategy that enhances the likelihood of ongoing usage of current and future pesticides for control of cotton jassid. Graphical abstract: Image 1 Highlights: Amrasca biguttula strain (Di-SEL) developed a 90-fold level of resistance to dimethoate. Inheritance mode of dimethoate resistance was polygenic, autosomal, and partially dominant. Di-SEL showed no cross-resistance to bifenthrin, imidacloprid, and chlorfenapyr. Our findings proved a keystone in insecticide resistance management programs of A. biguttula .